Nurses and Midwives as Global Partners to Achieve the Sustainable Development Goals in the Anthropocene. Issue 5 (31st May 2021) - Rosa, William E.; Catton, Howard; Davidson, Patricia M.; Hannaway, Catherine J.; Iro, Elizabeth; Klopper, Hester C.; Madigan, Elizabeth A.; McConville, Frances E.; Stilwell, Barbara; Kurth, Ann E.
Abstract: Purpose: To highlight ongoing and emergent roles of nurses and midwives in advancing the United Nations 17 Sustainable Development Goals by 2030 at the intersection of social and economic inequity, the climate crisis, interprofessional partnership building, and the rising status and visibility of the professions worldwide. Design: Discussion paper. Methods: Literature review. Findings: Realizing the Sustainable Development Goals will require all nurses and midwives to leverage their roles and responsibility as advocates, leaders, clinicians, scholars, and full partners with multidisciplinary actors and sectors across health systems. Conclusions: Making measurable progress toward the Sustainable Development Goals is critical to human survival, as well as the survival of the planet. Nurses and midwives play an integral part of this agenda at local and global levels. Clinical Relevance: Nurses and midwives can integrate the targets of the Sustainable Development Goals into their everyday clinical work in various contexts and settings. With increased attention to social justice, environmental health, and partnership building, they can achieve exemplary clinical outcomes directly while contributing to the United Nations 2030 Agenda on a global scale and raising the profile of their professions.